Salvage autologous transplant in relapsed multiple myeloma: long-term follow-up of the phase 3 GMMG ReLApsE trial - Bärtsch, Marc-Andrea; Schlenzka, Jana; Hielscher, Thomas; Raab, Marc-Steffen; Sauer, Sandra; Merz, Maximilian; Mai, Elias K.; Müller-Tidow, Carsten; Luntz, Steffen P.; Jauch, Anna; Brossart, Peter; Görner, Martin; et al. (Blood, 2025)
The multicenter, phase 3 German-Speaking Myeloma Multicenter Group (GMMG) ReLApsE trial randomized patients with relapsed and/or refractory multiple myeloma (RRMM) equally to lenalidomide/dexamethasone (LEN/DEX; 25 mg days 1-21, DEX 40 mg weekly, in 4-week cycles) reinduction, salvage high-dose chemotherapy (sHDCT; melphalan 200 mg/m2), autologous stem cell transplantation (ASCT), and LEN maintenance (10 mg/d; transplant arm, n = 139) vs continuous LEN/DEX (control arm, n = 138). Ninety-four percent of patients had received frontline HDCT/ASCT. We report an updated analysis of survival end points with a median follow-up of 99 months. Median progression-free survival (PFS) was 20.5 and 19.3 months in the transplant and control arm, respectively (hazard ratio [HR], 0.98; P = .9). Median overall survival (OS) was 67.1 and 62.7 months, respectively, (HR 0.89; P = .44). Landmark analyses from sHDCT and the contemporaneous LEN/DEX cycle 5 were performed because of 29% dropout of patients before sHDCT/ASCT in the transplant arm but did not reveal significant differences in PFS/OS. Time to progression after frontline HDCT/ASCT was a prognostic factor but did not predict benefit from sHDCT/ASCT. The GMMG ReLApsE trial does not support use of sHDCT/ASCT in RRMM after frontline HDCT/ASCT. This trial was registered at www.clinicaltrialsregister.eu as #EudraCT2009-013856-61.